Effectiveness of camera-based speed deterrence schemes and drivers' support for a hypothetical smartphone-App-based monitoring scheme - Mahdi Shehab (Transactions on Transport Sciences, 2022)
As the economic and health tolls resulting from traffic crashes continue to rise worldwide, the need to cut down on behaviours commonly recognized as contributing factors to crashes becomes vital. Speeding has been identified as a major contributing factor to the occurrence of crashes, with crash severity correlating strongly and positively with driving speed. This study represents an endeavour aiming to enhance traffic safety by addressing issues essential to improving the efforts usually undertaken to confront speeding drivers. The effectiveness of the current scheme of deterring speeding drivers in Kuwait relying mainly on automatic speed cameras was assessed through multiple linear regression analysis utilizing data elicited through self-report questionnaires. Moreover, drivers' support for a hypothetical scheme exploiting smartphone-Apps to constantly monitor driving behaviours of repeated traffic violators was measured. Such smartphone-App-based scheme symbolizes one of many possible innovative solutions that might utilize advances in mobile technologies and driver analytics to improve road safety. The findings from this study showed the current scheme to be ineffective based on reported behaviours by surveyed drivers. The study also demonstrated that the majority of surveyed drivers expressed support for the hypothetical scheme employing smartphone-Apps to provide continuous vigilance of driving behaviours for hazardous drivers. Analysis conducted via a proportional odds model demonstrated that support for the hypothetical scheme was less prominent among habitual speeders and frequent violators of speed limits as well as among young and male drivers.